Security frameworks in contemporary electronic government - Abassi, Ryma 1980; Ben Chehida Douss, Aida 1986 (Advances in electronic government, digital divide, and regional development (AEGDDRD) book series, 2019)
"This book addresses the difficulties and challenges faced in implementing e-government/m-government technologies and applications. It also addresses different aspects of security of e-government/m-government, ranging from big data issues, trust management, Blockchain technologies, and related topics"--Provided by publisher